The Effect of Understanding Tax Regulations, Tax Sanctions, and Awareness of Taxpayers on Compliance with Restaurant Taxpayers in Sumedang Regency - Nurul Apriliani Utami; Ayi Srie Yuniawati; Lilis Kartika (LPPM Universitas Sebelas April, 2020)
This research aim to knowthe influence of understanding tax regulation, tax sanction, awareness tax payers to compliance tax payers of restaurant at Sumedang Regency. This research uses quantitative research method by using a questionnaire as a data cellection media. Population of this research are taxpayer that registered in BAPPENDA Sumedang. The samples in this research are 53 restaurant taxpayers. The sample collection technique used in this research was purposive sampling Prerequisite test used classical assumption test.The data analysis techniques used in this research were multiple linear regression. This result indicated that (1) understanding tax regulation to compliance tax payers of restaurant tax payer, it is proven by the regression coefficient 0,389, the value of t amount>t table (2,789>2,00958) and significantly 0,008<0,05, (2) tax sanction to compliance tax payer of restaurant tax payer, it is proven by the regression coefficient 0,361, the value of t amount<t table (2,855>2,00958) and significantly 0,006<0,05, (3) awareness tax payers to compliance tax payers of restaurant tax payer, it is proven by the regression coefficient 0,467, the value of t amount<t table (3,288>2,00958) and significantly 0,002<0,05, (4) understanding tax regulation, sanction taxation, and awareness tax payers to compliance tax payers of restaurant tax payer F amount>F table (23,430>2,790) and significantly 0,000<0,05.